Impactos do Pibid no trabalho educativo dos supervisores - Andrade, Fernanda Borges de (2019)
The present work consisted of an effort to analyze which knowledges and practices serve as a foundation for the educational work of supervising teachers of the Pibid (Institutional Teaching Initiation Scholarships Program) who were scholarship students of the Program during the graduation course, seeking to understand how the experience in the Pibid has impacted on their professional practice and on their role as co-trainers of future teachers. When we decided to investigate what kind of knowledge and teaching practices Pibid has provided, we followed and analyzed the daily work of 07 supervisor-teachers who had been undergraduate students who participated in the Pibid as scholarship students of teaching initiation; this organization was related to the perspective inspired on the ethnography that we adopted and that seeks to analyze the socially configured phenomena. These supervisors participated in 06 sub-programs of the Pibid at UFTM and worked as co-trainers of undergraduate students, who participated in Pibid as scholarship students of teaching initiation, in 06 state schools in the city of Uberaba, in the state of Minas Gerais, during the year 2017. In the field work, we made observations of classes and meetings of these professionals with the scholarship students of teaching initiation, as well as interviews with the supervisors themselves. Through the present study, we confirm the importance of the school and the classroom as fundamental spaces and also of the exchange with the universities for the initial and continued formation of teachers, which demonstrates the great importance of the Pibid, making it possible not only to minimize the clash of reality for beginning teachers, but also to overcome the professional loneliness in which the active teachers find themselves, also allowing, above all, that knowledges and teaching practices arise from the dialogue between the subjects involved with teaching-learning around real questions in the disciplines to be taught, in the curricula and in the daily experiences of primary schools and universities. In this context we understand that Pibid was an experience that expanded and strengthened personal and professional knowledge through a work that involved dialogues, studies, readings, promotion and participation in events for teachers and students of the university and basic education, standing out as a fundamental aspect of the work carried out, an effective construction of relations between theory and practice. Keywords: Pibid. Teaching Formation. Pedagogical Practices. Theory-Practice relationship. School Routine.